GREEN PRODUCT PURCHASE DECISION: THE ROLE OF ENVIRONMENTAL CONSCIOUSNESS AND WILLINGNESS TO PAY - Firdaus, Ferry (Jurnal Aplikasi Manajemen, 2023)
This study aims to identify environmental consciousness and willingness to pay on the purchase decision of green products. Consumer's concern about environmental issues may not be easily translated into pro-environment behavior. Individuals with a strong belief that their environmental awareness behavior will result in something positive are more likely to engage in that behavior to support their concern for the environment. Through a survey of 263 respondents, this quantitative study finds that environmental awareness and environmental knowledge positively and significantly influence willingness to pay, and environmental attitude does not significantly influence willingness to pay. This study also finds that environmental awareness, environmental attitude, and willingness to pay positively and significantly influence green-product purchases, but environmental knowledge does not significantly influence green purchases. The study's practical contribution is that Indonesian organizations that are currently using or intend to use green product campaigns for commercial purposes can use the study's findings to better understand the ecosystem and create strategies that will increase the number of people using their green products. The study offers a new model with theoretical implications that take into account other factors that may affect consumers' decisions to make environmentally friendly purchases. Social influence, recycling participation, exposure to environmental messages through the media, and the value perceived by customers are some of the dimensions that can be added.